Artibeus glaucus (Chiroptera: Phyllostomidae). (30th December 2015) - Ortega, Jorge; Arroyo-Cabrales, Joaquín; Martínez-Mendez, Norberto; Del Real-Monroy, Melina; Moreno-Santillán, Diana; Velazco, Paúl M.
Abstract: The silvery fruit-eating bat ( Artibeus glaucus Thomas, 1893 ) is a small sized phyllostomid bat with indistinct facial stripes and obscure pale edging on the ears, dark brown pelage with less contrast on the shoulders and venter, and dorsal fur that extends beyond the posterior margin of the uropatagium. It has a narrow distribution associated with intermediate elevations (200–2, 000 m) in the Andean Mountains, mainly in Ecuador, Peru, and Bolivia. It has also been found to inhabit lowland areas but not in high numbers. A. glaucus is classified as "Least Concern" by the International Union for Conservation of Nature and Natural Resources.